Data-driven learning and teaching of colligations of prepositions : the case of law undergraduates in Malaysia / Kamariah binti Yunus - Yunus, Kamariah (2015)
Data-Driven Learning (DDL) is the pedagogic application of corpus linguistics in classrooms. This study examines the impact of guided DDL (paper-based and online searching) on law undergraduates’ colligational competence, i.e. colligations of prepositions, one of the most essential lexico-grammatical components in legal texts. Firth’s (1957b) contextual theory of meaning and Vygotsky’s scaffolding theory (1978) become the premises of this study. Forty semester three law undergraduates in the Faculty of Law and International Relations (FLAIR), UniSZA, Malaysia took part in the seven-week experimental study. Data were collected from the pretest and posttest and analysed using the Mann-Whitney U test to find differences between the two group scores. A post- experimental interview was later conducted with 10 respondents in the experimental group to gain their perceptions of the DDL approach. The findings show that the students in the DDL group performed significantly better than the students in the comparison group in the knowledge of the form and meaning of colligations of prepositions, but not in the production. The results of the study indicate that multiple exposures to DDL during the seven-week experimental course impacted the respondents’ receptive knowledge but not the production (single-sentence) of colligations of prepositions. Meanwhile, the results from the post-course interview show that the majority of the 20 respondents had positive attitudes towards DDL. It was concluded that explicit exposure to DDL may affect greatly the knowledge of colligations of prepositions among ESP or law students. However, before the input becomes output (spoken or written production), it requires a lot of time and practice. The learners’ positive attitudes towards DDL can be explained in terms of inductive and motivating approach that DDL brings to classrooms. This study recommends explicit teaching of colligations of prepositions via paper-based and guided DDL online as opposed to the conventional approach and ‘hard DDL’ (independent online searching) to enhance law students’ colligational competence.